Decrease in wind stress leads to an increase in the above ground morphology and number of seeds of an invasive alien species, Bidens pilosa (Asteraceae) - Shiba, Masayuki; Kobayashi, Nagisa; Harada, Shiori; Fukuda, Tatsuya (Frontiers in Plant Science, 2024)
We conducted comparative analyses using an open-top chamber (OTC) to reduce wind stress to clarify the impact of decreased wind stress on the invasive species Bidens pilosa L. (Asteraceae), which ranks among the worst 100 species on the Invasive Alien Species List in Japan. Morphological analyses revealed that the number and size of leaves in the OTC group were significantly higher than those in the control group (wind). There was also a significantly higher investment in stems in the former than in the latter. No significant differences were observed in root dry mass; however, the resource allocation ratio to the roots was significantly higher in the wind group than in the OTC group. Although the total seed mass was greater in the OTC group, there were no significant differences in the ratio of resource allocation to seeds between the groups, and no significant differences were observed in the mass of each seed. However, the number of seeds was significantly higher in the OTC group. Adaptive changes in the leaves, stems, and roots to avoid and/or resist wind were reflected in differences in the number of seeds. In addition, a decrease in wind stress contributed to an increase in the number of seeds in B. pilosa. Such mechanisms are likely widespread because B. pilosa is often highly abundant in urban systems.